The co-creation edge: harnessing big data to transform sales and procurement for business innovation - Gouillart, Francis J.; Quancard, Bernard (Palgrave Macmillan, 2016)
Rapid changes in business along with better informed customers threaten the traditional sales and procurement process. Thousands of sales and procurement people are threatened with extinction, yet all is not destined to be doom and gloom. A new way of partnering between these two roles can, in fact, create significant value for both organizations. Sales and procurement professionals have a bright future ahead of them if they can respond to six trends that the authors have identified in the business-to-business world. Each trend offers an opportunity to develop a new skill for sales and procurement professionals and adopt a new practice. Because these practices are not yet widely adopted as "best practices", the authors coin them "next practices." These trends include: working together to solve complex problems; organizing problem-solving networks across company boundaries; creating processes for live cross-company engagement; facilitating data driven, cross-company interactions fed by digital platforms; providing new personal experiences for individuals and lastly (and most importantly) creating new sources of value for firms. If these trends are adopted by organizations, the ability to co-create means providing significant value to both the sales management team at the supplier and the purchasing management team at the customer. With the alternative being that these job functions will be replaced by web-based or channel-based alternatives that will do most of what they do today at a fraction of the cost. Increasingly, there is no middle ground anymore. SAMs and senior buyers will either evolve into high value-added sales and procurement professionals, or disappear.
Keywords: Co-création; Réservé UdeM